2012
DOI: 10.3109/08923973.2011.649288
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences on immunostimulatory activity of raw and black garlic extract in human primary immune cells

Abstract: The immunostimulatory activities of garlic extract using a cell line or animal models have been reported; however, no previous studies have evaluated individual differences in regards to the immunostimulatory activities. The immunostimulatory activities such as cell proliferation, tumor necrosis factor (TNF-α) and nitric oxides (NO) production of raw garlic and black garlic extracts on individual primary lymphocytes or macrophages isolated from the blood of 21 volunteers were evaluated. The antioxidant and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
0
18
0
3
Order By: Relevance
“…Increasing antioxidant, phenol and flavonoid are due to phenol oxidation process. Such process is in line with the increasing of antitumor effect (Wang et al 2012) and immunostimulatory activity (Purev et al 2012). S-allyl-cystein is the special product from phenol oxidation and plays an essential role in black garlic's pharmacological effects (Ngan et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Increasing antioxidant, phenol and flavonoid are due to phenol oxidation process. Such process is in line with the increasing of antitumor effect (Wang et al 2012) and immunostimulatory activity (Purev et al 2012). S-allyl-cystein is the special product from phenol oxidation and plays an essential role in black garlic's pharmacological effects (Ngan et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…In the primary lymphocytes isolated from human blood, the treatment with 70% ethanolic BG extracts led to an increased level of cell proliferation in all the individual B-lymphocytes or Tlymphocytes (Purev, Chung, & Oh, 2012). The increases in the level of released TNF-protein and the production of NO in macrophage samples further confirmed the immunostimulatory activity of BG in human primary lymphocytes and macrophages (Purev et al, 2012). Feng et al (2010) evaluated the pharmacological benefits of BG extracts to the BALB/c mice, and found that BG extracts enhanced significantly the cytotoxicity of nature killer cells and promoted the secretion levels of NO, TH1 cytokines IL-2, TNF-, and TNF-.…”
Section: Immunostimulatory Activitymentioning
confidence: 98%
“…Some cell lines and animal models have been used to study the immune‐enhancing properties of BG extract. In the primary lymphocytes isolated from human blood, the treatment with 70% ethanolic BG extracts led to an increased level of cell proliferation in all the individual B‐lymphocytes or T‐lymphocytes (Purev, Chung, & Oh, ). The increases in the level of released TNF‐α protein and the production of NO in macrophage samples further confirmed the immunostimulatory activity of BG in human primary lymphocytes and macrophages (Purev et al., ).…”
Section: Nutritional Value and Biological Activity Of Bgmentioning
confidence: 99%
“…The study demonstrated that 47 kDa protein purifi ed from aged garlic could be considered as a potential candidate to generate tolerogenic dendritic cells in-vitro. The 70 % ethanol black garlic extracts (BGE) at 70 °C for 12 hours showed the strongest antioxidant and anticancer activities (Purev et al 2012 ). It was found that the cell proliferation, TNF-α and NO production of primary immune cells obtained from volunteers' blood treated with 70 % raw garlic extract (70 % RGE) were signifi cantly different; however, little difference was observed for the 70 % BGE treatment.…”
Section: Immunomodulatory/ Haemagglutination Activitymentioning
confidence: 87%